Designs from the eighties. Spanish delta awards vs. MOMA’s online catalogue - Rios-Moyano, Sonia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
We will deal with the most iconic designs “made in Spain” during the boom decade of the eighties. However, our contribution lies in relating them to the international design of that same decade, taking as a reference the designs that won prizes in the Delta Awards for Spanish design and the MoMA collection (available online), since it is a reference in that it was one of the first contemporary art museums to museumise design objects and to value their aesthetic component, their functionality, and their technological innovation.